Consensus on definition and severity grading of lymphatic complications after kidney transplantation. Issue 7 (30th March 2020) - Mehrabi, A; Kulu, Y; Sabagh, M; Khajeh, E; Mohammadi, S; Ghamarnejad, O; Golriz, M; Morath, C; Bechstein, W O; Berlakovich, G A; Demartines, N; Duran, M; et al.
Abstract: Background: The incidence of lymphatic complications after kidney transplantation varies considerably in the literature. This is partly because a universally accepted definition has not been established. This study aimed to propose an acceptable definition and severity grading system for lymphatic complications based on their management strategy. Methods: Relevant literature published in MEDLINE and Web of Science was searched systematically. A consensus for definition and a severity grading was then sought between 20 high-volume transplant centres. Results: Lymphorrhoea/lymphocele was defined in 32 of 87 included studies. Sixty-three articles explained how lymphatic complications were managed, but none graded their severity. The proposed definition of lymphorrhoea was leakage of more than 50 ml fluid (not urine, blood or pus) per day from the drain, or the drain site after removal of the drain, for more than 1 week after kidney transplantation. The proposed definition of lymphocele was a fluid collection of any size near to the transplanted kidney, after urinoma, haematoma and abscess have been excluded. Grade A lymphatic complications have a minor and/or non-invasive impact on the clinical management of the patient; grade B complications require non-surgical intervention; and grade C complications require invasive surgical intervention. Conclusion: A clear definition and severity grading for lymphatic complications after kidney transplantation was agreed. The proposed definitions should allow better comparisons between studies. Graphical Abstract: A clear definition and severity grading for lymphatic complications after kidney transplantation is proposed based on the management strategy. The proposed definition and three-level grading system are generally reasonable, not complicated, and easy to understand; they will allow standardization of results relating to lymphatic complications after kidney transplantation and better comparisons between studies. Valuable consensus